2018
DOI: 10.21726/rsbo.v1i3.489
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of methodologies for valuation of esthetic damage and the forensic application in Brazil

Abstract: Introduction: The esthetic damage is any pejorative modification in static or dynamic expression, perceived by any sense, affecting the image of the person. The esthetic damage repair has legal support in Brazilian legislation. Objective: to systematize the different existing methods for valuation of esthetic damages, critically analyze their characteristics, advantages and disadvantages; and evaluate whether these methods would have been validated in any population inside or outside of Brazil. Literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In our study, we aimed to identify some of the factors that contribute to the psycho-social distress of the person with post-traumatic scarring. For this purpose, we employed a morphological scale (POSAS) in association with other scales such as MPIS, conceived to measure the self-reported, subjectively assessed social support in patients with scars [ 17 ], the Hopeless Depression Symptom Questionnaire (HDSQ), designed to measure hopelessness/depression [ 22 ], and the Multidimensional Scale of Perceived Social Support (MSPSS), that quantifies the self-reporting of subjectively assessed social support [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we aimed to identify some of the factors that contribute to the psycho-social distress of the person with post-traumatic scarring. For this purpose, we employed a morphological scale (POSAS) in association with other scales such as MPIS, conceived to measure the self-reported, subjectively assessed social support in patients with scars [ 17 ], the Hopeless Depression Symptom Questionnaire (HDSQ), designed to measure hopelessness/depression [ 22 ], and the Multidimensional Scale of Perceived Social Support (MSPSS), that quantifies the self-reporting of subjectively assessed social support [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bodily harm can be evaluated, but for the elements of moral suffering there are no objective criteria. Evaluation scales have difficulty in assessing the role of mental suffering, given their process of development, modifying sometimes, the physiognomy or even the victim’s aesthetic perception of its own body [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The standard procedure of the forensic doctor is to write in detail the morphological characteristics of the scar and eventually to take pictures if there is any doubt about the identity of the person. Scars that affect areas of importance in expressing nonverbal language or those that alter the natural symmetry of the face lead to aesthetic damage [5]. To be successful, an aesthetic intervention should represent the optimal balance between science, the art of plastic surgery, and the patient's expectations, as well as good communication between the surgeon and the patient [6].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Facial scars are considered aesthetic damage that causes unpleasant modifications in both the static or dynamic facial expression recognized by everyone and affect the image of the person. 3 It is reported that people who have symmetrical faces are more attractive to the opposite sex than those with asymmetrical faces and the social interactions with both sexes are easier. 4 It is also known that anxiety and depression caused by the trauma of the face, increase with the healing process delay.…”
Section: Introductionmentioning
confidence: 99%